2017
DOI: 10.24875/ric.17002125
|View full text |Cite
|
Sign up to set email alerts
|

Activated and Micronized Zeolite in the Modulation of Cellular Oxidative Stress in Mexican Smokers: A Randomized Clinical Trial

Abstract: Background: Activated and micronized zeolites are used as detoxifying agents in humans. Detoxification is attributed to their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Activated and micronized zeolites are used as detoxifying agents in humans. Detoxification is attributed to their ability to reduce lipid peroxidation by scavenging free radicals [ 13 ]. In the present study, the effect of supplemental zeolite on antioxidant status of turkey are shown in Table 6a and Table 6b .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated and micronized zeolites are used as detoxifying agents in humans. Detoxification is attributed to their ability to reduce lipid peroxidation by scavenging free radicals [ 13 ]. In the present study, the effect of supplemental zeolite on antioxidant status of turkey are shown in Table 6a and Table 6b .…”
Section: Resultsmentioning
confidence: 99%
“…Activated and micronized zeolites are used as detoxifying agents in humans. Detoxification is attributed to their ability to reduce lipid peroxidation by scavenging free radicals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in healthy volunteers, in both a smoker and a non-smoker group, Dogliotti and colleagues demonstrated that natural zeolites, such as chabazite, phillipsite, and analcime, administered perorally for 4 weeks, increased the blood levels of gluthatione peroxidase, superoxide dismutase, and gluthatione reductase and reduced lipid peroxidation [ 224 ]. Next, in a randomized, double-blind clinical trial on smokers, it was further shown that micronized and activated natural zeolite increased catalase activity and decreased H 2 O 2 levels accompanied by a reduction in lipid peroxidation [ 225 ].…”
Section: Antioxidative Properties Of Zeolitementioning
confidence: 99%